2022
DOI: 10.1007/s10711-022-00702-w
|View full text |Cite
|
Sign up to set email alerts
|

Virtually special non-finitely presented groups via linear characters

Abstract: We present a new method for showing that groups are virtually special. This is done by considering finite quotients and linear characters. We use this to show that an infinite family of groups, related to Bestvina-Brady groups and branching, provides new examples of virtually special groups outside of a hyperbolic context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…One should compare this to [15], where a similar construction is applied to generalised Bestvina-Brady groups. There it is shown that if H W is virtually torsion-free, then the set of relators for which p-th powers are taken has to be periodic.…”
Section: Introductionmentioning
confidence: 99%
“…One should compare this to [15], where a similar construction is applied to generalised Bestvina-Brady groups. There it is shown that if H W is virtually torsion-free, then the set of relators for which p-th powers are taken has to be periodic.…”
Section: Introductionmentioning
confidence: 99%